2022
DOI: 10.1002/pits.22753
|View full text |Cite
|
Sign up to set email alerts
|

Examining the implementation of Teacher–Child Interaction Training‐Universal in public schools

Abstract: The Teacher–Child Interaction Training‐Universal (TCIT‐U) is a professional development program for teachers that promotes positive relational interactions and strengthens classroom management. This study examines the implementation of TCIT‐U in a public school district to guide future implementation and sustainability. This study uses qualitative methods to examine the implementation of TCIT‐U across preschool through second‐grade classrooms in a suburban public school district in Illinois, United States. Eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Numerous studies have demonstrated that Teacher-Child Interaction Training has promising success for improving teacher-child interactions and teacher's effective behavior management skills (Budd et al, 2016;Davidson et al, 2020;Fawley et al, 2020; Page 10 of 14 17:12 Fernandez et al, 2015;Fernandez et al, 2015;Garbacz et al, 2014;Lyon et al, 2009;Santiago et al, 2022). To the authors' knowledge, this was the first quasi-experimental study that explored how TCIT-U affects teachers' sense of self-efficacy among a predominately Hispanic (96.4%) teacher population in the United States.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Numerous studies have demonstrated that Teacher-Child Interaction Training has promising success for improving teacher-child interactions and teacher's effective behavior management skills (Budd et al, 2016;Davidson et al, 2020;Fawley et al, 2020; Page 10 of 14 17:12 Fernandez et al, 2015;Fernandez et al, 2015;Garbacz et al, 2014;Lyon et al, 2009;Santiago et al, 2022). To the authors' knowledge, this was the first quasi-experimental study that explored how TCIT-U affects teachers' sense of self-efficacy among a predominately Hispanic (96.4%) teacher population in the United States.…”
Section: Discussionmentioning
confidence: 93%
“…Professional development and in-service training can positively influence teacher selfefficacy (Bray-Clark & Bates, 2003;Santiago et al, 2022;Toran et al, 2017). For many educators who do not participate in formal preparation programs, in-service training often overlaps as default preparation for practice (Institute of Medicine & National Research Council, 2015).…”
Section: Teacher Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The teacher training program was capable of boosting the interest of teachers in the teaching and learning process and improving the quality of teaching and learning. A qualitative approach was utilized in suburban public schools in Illinois, USA to examine the effectiveness of teacher-student interaction training in improving classroom management and interaction, according to the literature [15]. The results show that teachers and students can achieve effective communication and interaction under the training, and to a certain extent, teachers' confidence and self-efficacy in teaching were enhanced.…”
Section: Introductionmentioning
confidence: 99%